The construct validity and reliability of the Turkish version of Spreitzer's psychological empowerment scale - Turan Sevgi; Uner Sarp (BMC, 2010)
Abstract Background Today, many organizations have adopted some kind of empowerment initiative for at least part of their workforce. Over the last two decades, two complementary perspectives on empowerment at work have emerged: structural and psychological empowerment. Psychological empowerment is a motivational construct manifested in four cognitions: meaning, competence, self-determination and impact. The aim of this article is to examine the construct validity and reliability of the Turkish translation of Spreitzer's psychological empowerment scale in a culturally diverse environment. Methods The scale contains four dimensions over 12 statements. Data were gathered from 260 nurses and 161 physicians. The dimensionality of the scale was evaluated by exploratory factor analyses. To investigate the multidimensional nature of the empowerment construct and the validity of the scale, first- and second-order confirmatory factor analysis was conducted. Furthermore, Cronbach alpha coefficients were assessed to investigate reliability. Results Exploratory factor analyses revealed that four factors in both solutions. The first- and second-order factor analysis indicated an acceptable fit between the data and the theoretical model for nurses and physicians. Cronbach alpha coefficients varied between 0.81-0.94 for both groups, which may be considered satisfactory. Conclusions The analyses indicated that the psychometric properties of the Turkish version of the scale can be considered satisfactory.